Cameras for conservation: wildlife photography and emotional engagement with biodiversity and nature. Issue 3 (4th May 2019) - Hanisch, Emma; Johnston, Ross; Longnecker, Nancy
ABSTRACT: Biodiversity loss is a major ecological threat, but relatively few people are directly engaged with the problem. In this exploratory research, we studied relationships between photographing wildlife and engagement with biodiversity and nature. In an online survey, we randomly assigned participants ( n = 182) to photograph wildlife, observe wildlife without photographing, or do nothing (Control). Participants responded to items measuring engagement in four categories: emotional attachment, awareness/knowledge, environmental concern, and wildlife interest. The Photography group scored higher than the other groups in attachment and concern, but not in awareness or interest. This suggests that photographing wildlife may increase emotional engagement, but not cognitive engagement. However, responses to qualitative questions indicated that the Observations group learned more information about biodiversity than did the Photography group. Photography may be a useful tool for increasing emotional engagement with biodiversity and nature; it should be coupled with other activities to promote cognitive engagement.